Pollution reduction in an eco-friendly chrome-free tanning and evaluation of the biodegradation by composting of the tanned leather wastes. (15th January 2015) - Zuriaga-Agustí, E.; Galiana-Aleixandre, M.V.; Bes-Piá, A.; Mendoza-Roca, J.A.; Risueño-Puchades, V.; Segarra, V.
Abstract: Chromium is one of the most important environmental concerns related to tanneries. The most often used process for hide tanning is chrome tanning. This implies the presence of chromium both in wastewaters and in leather wastes. Leather wastes have to be disposed in landfills what entails a considerable environmental impact and high cost. In this work, a study about the effect of a chrome-free tanning process using titanium salts instead, on the wastewater and on the solid wastes has been performed. In this way, a study of biodegradation of leather waste samples tanned with different tanned agents by composting together with food wastes is carried out in a laboratory composter. Results indicated that leather tanned with titanium salts met the required quality standards. Besides, the concentration of organic matter and salts in the tannery process wastewater was lower comparing with the chromium tanning agent. In the biodegradation study by composting, leather samples tanned with titanium were degraded, reducing around 10% the carbon content with the subsequent diminution of the C/N ratio. In addition, the size was reduced 41% in 45 days. However, leather sample tanned with oxazolidine was partially degraded in the composter; meanwhile chrome and vegetable tanned leather kept inalterable. Highlights: Titanium tanned hides reached the quality standard values for leather. Wastewaters from titanium tanning were less pollutant than the chrome tanning. Composting of leather with food wastes is a promising alternative to landfills. Size reduction near 50% was achieved with titanium tanned hide in composter. No biodegradation was observed for chrome tanned hides.